Mapping release and propagation areas of permafrost-related rock slope failures in the French Alps: A new methodological approach at regional scale ... - Cathala, M.; Magnin, F.; Ravanel, L.; Dorren, Luuk; Zuanon, N.; Berger, F.; Bourrier, F.; Deline, P. (Elsevier, 2024)
Rock slope failure (RSF) from permafrost-affected rockwall is an emerging threat for human lives and infrastructure which raises a need for RSF hazard assessments in the alpine environment. This study proposes the first mapping approach to RSF release and propagation areas in the French Alps. By analysing a unique RSF database (1389 recent events in the Mont Blanc massif), we determine three levels of RSF Susceptibility Indexes (RSI) to map the potential release areas. We highlight a strong correlation between RSF and permafrost: 99 % of RSFs occurred from rockwalls with a Mean Annual Rock Surface Temperature (MARST) ≤ 3 °C and 35 % with MARST from −2 to 0 °C. The release area maps (34 km2 to 284 km2 depending on the RSI) are entered into a simple propagation model (RockavELA), using a dimensionless area-based energy line principle (i.e. reach susceptibility) to map propagation areas of potential RSFs. Three propagation limits are proposed, fitting the propagation characteristics of another RSF database ...